Atuação em política ou atuação profissional: revelações e contradições de um plano de carreira - Pereira, Gilda Alessandra da Trindade (Universidade Federal de São Carlos, 2024)
Academic research frequently examines the actions of education professionals, mainly related to early childhood education, due to its public policy dimensions. In light of the creation of such public policies, this research addresses a key problem: how do the public policies of Araçatuba municipality impact the actions of professionals in early childhood education institutions? This question is aligned with the broader goal of analyzing the impacts caused by the elaboration of the Career Plan LC nº 288 (Araçatuba 2022) on professionals working in early childhood education institutions in the city. The research adopts a descriptive-exploratory approach, using the policy cycle analysis of Ball and Bowe (1994) and Mainardes (2006), as well as the Action Theory of Ball, Maguire, and Braun (2016). Furthermore, contributions from Rosemberg (2003, 2015, 2021) and Kramer (2006, 2007, 2013, 2015) were included, among other theorists. The study was conducted from a critical-reflexive perspective, adopting an ethical-onto-epistemological position (Mainardes, 2022), which acknowledges that studies on educational policies involve epistemological, ontological, and ethical considerations. This perspective proposes a unification between theoretical conceptions and ethical behavior, considering the coherence between being, knowing, and acting as a researcher. The methodological procedures involved bibliographic research and document analysis, which addressed historical processes and the consolidation of policies in the professional field of early childhood education in Brazil and the municipality where the research was conducted. Among the results, negative impacts were evident, related to professional devaluation, training policies, early childhood education objectives, and the incompatibility of the municipality's policies with national policies regarding basic education.
Policy engagement or professional pratice: insights and inconsistency from a career plan
Keywords: Profissionais da educação infantil; Políticas públicas; Plano de carreira; Early chidhood education professionals; Public policies; Career plan; CIENCIAS HUMANAS::EDUCACAO::ADMINISTRACAO EDUCACIONAL; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO